Assessment of Surface Water Quality in Peel Harvey Region, Western Australia - Anwar, Faisal; Wong, Matthew (Engineers Australia, 2011)
The water bodies of Peel Harvey region in Western Australia were selected to assess theirsurface water quality using statistical methods. Six water quality parameters such as, total phosphorus(TP), total nitrogen (TN), salinity, turbidity, pH and dissolved oxygen (DO) together with temperaturefor each samples from 18 monitoring sites (n=9895) were collected from the Department of Water for2001-2009. First, normality of data was checked using box plot and histogram and found that pH andDO showed normal distribution and TP and TN showed log normal distribution respectively. Next,multivariate statistical analyses were performed and multivariate cluster dendrogram shows the spatialrelationship of water quality based on the changes in nutrient characteristics of different rivers.Multivariate discriminate analysis shows that TN, TP and DO are significant in high polluted sites ofthe water bodies. Multivariate factor analysis showed that Serpentine river has severe pollution of TNwhere as Murray river has the severity of TP.